Acute Kidney Injury, Microvascular Rarefaction, and Estimated Glomerular Filtration Rate in Kidney Transplant Recipients - Doreille, Alice (Clin J Am Soc Nephrol, 2021)
BACKGROUND AND OBJECTIVES: Animal studies suggest that microvascular rarefaction is a key factor in the acute kidney disease to CKD transition. Hence, delayed graft function appears as a unique human model of AKI to further explore the role of microvascular rarefaction in kidney transplant recipients. Here, we assessed whether delayed graft function is associated with peritubular capillary loss and evaluated the association between this loss and long-term kidney graft function. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: This observational, retrospective cohort study included 61 participants who experienced delayed graft function and 130 who had immediate graft function. We used linear regression models to evaluate associations between delayed graft function and peritubular capillary density expressed as the percentage of efficient cortical area occupied by peritubular capillaries in pre- and post-transplant graft biopsies. eGFRs 1 and 3 years post-transplant were secondary outcomes. RESULTS: Post-transplant biopsies were performed at a median of 113 days (interquartile range, 101–128) after transplantation. Peritubular capillary density went from 15.4% to 11.5% in patients with delayed graft function (median change, −3.7%; interquartile range, −6.6% to −0.8%) and from 19.7% to 15.1% in those with immediate graft function (median change, −4.5%; interquartile range, −8.0% to −0.8%). Although the unadjusted change in peritubular capillary density was similar between patients with and without delayed graft function, delayed graft function was associated with more peritubular capillary loss in the multivariable analysis (adjusted difference in change, −2.9%; 95% confidence interval, −4.0 to −1.8). Pretransplant peritubular capillary density and change in peritubular capillary density were associated with eGFR 1 and 3 years post-transplantation. CONCLUSIONS: Perioperative AKI is associated with lower density in peritubular capillaries before transplantation and with loss of peritubular capillaries following transplantation. Lower peritubular capillary density is linked to lower long-term eGFR.